Plasma phospho-tau 217 outperforms plasma phospho-tau 181 analyzed with Lumipulse in detecting Alzheimer’s dementia in a real-world memory clinic population - Defrancesco, Michaela; Gizewski, Elke R.; Steiger, Ruth; Virgolini, Irene; Kroiss, Alexander; Schurr, Timo; Görtz, Jan Paul; Marksteiner, Josef; Hofer, Alex; Humpel, Christian (Frontiers in Aging Neuroscience, 2026)
IntroductionWe need easy-to-use, valid biomarkers for diagnosing Alzheimer’s disease (AD). Blood biomarkers are a promising option, especially as there is a good correlation with beta-amyloid and tau biomarkers measured by positron emission tomography or in the cerebrospinal fluid. We investigated the added value of measuring these markers in the blood of patients who have already been diagnosed, and how cut-off values can be set in clinical routine.MethodsPlasma pTau 181 and pTau 217 levels were analyzed using Lumipulse G600II in 132 memory clinic outpatients with different forms of dementia and in 43 cognitively intact controls (CIC). Linear discriminant analysis was used to determine the diagnostic accuracy of pTau 181, pTau 217, and the pTau 217/181 ratio in plasma. The Youden index (YI) was calculated to determine optimal cut-points.ResultsThe diagnostic performance of pTau levels to distinguish between dementia patients and CIC yielded an AUC of 0.724 (95% CI: 0.635–0.813) with a cut point (YI) of 1.46 pg/mL for pTau 181 and an AUC of 0.845 (95% CI: 0.763–0.927) with a cut point (YI) of 0.23 pg/mL for pTau 217. The pTau217/181 ratio showed slightly better discriminatory performance (AUC of 0.858 [95% CI: 0.769–0.946]) at a cut point (YI) of 0.18.DiscussionWe suggest that the combined use of pTau217 and pTau181 as a ratio may serve as a valuable method to differentiate AD from non-AD dementia and from cognitively healthy individuals. However, plasma pTau217 outperforms pTau181 and the ratio due to its greater stability and marginally higher sensitivity compared to the 217/181 ratio. Plasma pTau217 levels above the cut-off point could indicate the need for further investigation of biomarkers.